Racialización estructural e inequidad del estado de salud de pacientes con drepanocitosis en Colombia. - MARTÍNEZ-BETANCUR, OCTAVIO (Acta Medica Colombiana)
When the State’s institutional structure operates a racially stratified healthcare system, it contributes to an unequal distribution of health outcomes: structural State racism. We analyze the State of Colombia´s affirmative and restorative action that included sickle cell disease as orphan disease number 751 through Resolution 2048 of 2015 by the Ministry of Health and Social Protection, under Law 1392 of 2010, as an institutional racialization process that establishes healthcare inequalities in the population of affected patients.